Estudio de prefactibilidad para la instalación de una planta productora de hojuelas de maíz morado (Zea mays l.) - Ortega Alvino, Lesley Alessandra (2021)
The objective of the present research is determinate the market, technical, economic, financial, and social viability for the installation of a purple corn flakes plant. The product will have a presentation in bags of 200 grams. The target market will be Metropolitan Lima, which represents 32,6% of the population of Peru. At the level of socioeconomic segmentation, the sectors chosen are A and B. At the level of behavioral segmentation, the Millennial generation (18 - 39 years old) from sector A and B of Metropolitan Lima have been chosen for their openness to new products and Lifestyle. This generation represents 36,88% of the population. The sale value to the modern channel distributors will be S /. 3,03 per bag, and the price to the final consumer will be S /. 5,50 per bag of 200 grams. The production plant will be installed in the district of Lurin in Metropolitan Lima, selected for its suitable location with the supplier and distribution centers of the supermarkets. The plant size is 71,75 kg / h of final product. On the other hand, the technology required to produce the products is feasible to acquire and use. Regarding investment, this amounts to S/. 2.291.744,12. A financing of 39% of the investment was considered, which includes the construction of the plant. The debt horizon is 6 years, and an effective rate of 11,50% with increasing installments. The economic evaluation establishes S/. 1.032.096,94 of net present value, 23,5% of internal rate of return, 1,45 of benefit-cost relation and a recovery period of 5 years, 2 months and 16 days. The financial evaluation establishes S/. 1.229.592,91 of net present value, 31% of internal rate of return, 1,88 of benefit-cost relation and a recovery period of 4 years, 11 months and 3 days. Finally, in relation to the social evaluation, the added value amounts to S/. 12.109.122 and a total investment ratio of 5.28 soles is achieved for each sol invested.